2021
DOI: 10.1177/0300060521990127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional risk on cognitive function in patients with chronic obstructive pulmonary disease

Abstract: Objective We aimed to clarify the cognitive function of patients with chronic obstructive pulmonary disease (COPD) and different nutritional status. Methods Among 95 patients with COPD in this retrospective study, we administered the Nutritional Risk Screening 2002 (NRS 2002) and Mini-Mental State Examination (MMSE). We recorded patients’ clinical characteristics, comorbidities, and laboratory measurements. According to NRS 2002 scores, patients were divided into two groups: no nutritional risk with NRS 2002 &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Our data showed that only 28.2% of the COPD patients were at nutritional risk, which was lower than the proportions in previous studies (35.2–54.8%) ( 13 , 32 34 ). However, we observed that COPD was still the third leading cause of high nutritional risk in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…Our data showed that only 28.2% of the COPD patients were at nutritional risk, which was lower than the proportions in previous studies (35.2–54.8%) ( 13 , 32 34 ). However, we observed that COPD was still the third leading cause of high nutritional risk in our study.…”
Section: Discussioncontrasting
confidence: 90%
“…At the same time, the study by Huang et al explores the impact of malnutrition on cognitive function, showing a negative correlation between MMSE scores and nutritional risk [ 89 ]. This emphasizes the need for nutritional assessments and interventions as an integral part of managing chronic respiratory diseases, underscoring malnutrition as an independent risk factor for cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Among others this high prevalence of undernutrition is caused by poor dietary quality and lifestyle habits, decreased dietary intake due to anorexia and early satiety, and increased energy expenditure related to circulating factors such as hormones, adipokines, and inflammatory cytokines. Undernutrition and micronutrient deficiencies have been associated with neurodegeneration, and COPD patients with increased nutritional risk are more likely to have cognitive impairment ( 16 ).…”
Section: Introductionmentioning
confidence: 99%